Ethnobotanical and toxicology study of medicinal plants used for the treatment of diabetes in the High Atlas Central of Morocco - Souad Belhaj; Noureddine Chaachouay; Lahcen Zidane (GarVal Editorial Ltda., 2021)
Context: Diabetes mellitus is considered one of the scourges of the third millennium in the world for several years. Aims: To evaluate, identify and preserve the experiences gained over the centuries. It is about therapeutic use of medicinal plants exploited for the treatment of diabetes, and to clarify its toxicities, in order to sensitize the population of the High Atlas Central (HAC) of Morocco not only on the risk but also the benefit of the use of phytotherapy. Methods: The surveys ethnopharmacological were conducted 834 the interviewees, using semi-structured survey, by application of quantitative indices such as Consensus index (CI %), Use value (UVi), family UV (FUV), relative frequency of citation (RFC), plant part value (PPV), and informant consensus factor (ICF) to assess the exact value of medicinal plants (MP). Results: We found that 144 medicinal plants in 121 genera and 52 plant families were traditionally used to treat diabetes, of which seven species were endemic to the study area, and 32 were being cited first ever to treating diabetes. In addition, we collected toxicological information on 99 antidiabetic plants, of which 41 species showed no toxic activity and 43 were toxic and sometimes lethal in high doses. The Ranunculaceae family showed the highest use value (FUV =0.139). Leaves were the most used plant parts (PPV =0.282) and infusion was the dominant method of preparation. The frequently used species were Olea europaea L. (UVi =0.172), Salvia officinalis L. (UVi =0.156) and Euphorbia resinifera Berg (UVi =0.150). Conclusions: These results are a rich source of information. They contribute to the knowledge of the antidiabetic medicinal flora of our study area, and to the preservation of the local popular know-how of the word that tends to disappear. They may also represent a database that consists of purifying and identifying the characterization of active compounds of herbal extracts with antidiabetic activity.